Hubungan K-pop Idol Sebagai Brand Ambassador terhadap Keputusan Pembelian Followers - Santy Widiadamayanti; Indri Rachmawati (UNISBA Press, 2022)
Abstract. Competition to attract consumers to companies in Indonesia is getting tougher, especially for marketplace companies. Various ways are carried out by companies to increase consumers, one of which is making Kpop Idol as a Brand Ambassador. This study takes the title